Effects of Information Overload on Hostile Behaviors Online - 진상형; 이철; 장영빈 (한국전자거래학회지, 2019)
Although there have been lots of studies about users’ behaviors online, few have explored the mechanism of hostile behaviors. In this sense, this study aims at discovering what may elevate users’ hostile behaviors. More specifically, we tried to find the relationship between flaming behavior and perception factors such as perceived risk, anonymity and expected emotional reaction. A survey was conducted to investigate the relationship of the above variables. As a result, all these variables show significant effects on flaming, and information overload are found to act as a moderator. We carefully conclude that flaming in online community can be reduced by preventing information overload each user perceives.
Keywords: Flaming; Information Overload; Public Self-Awareness; Perceived Identifiability; Affective Social Presence; 악성댓글; 정보과부하; 공적 자기인식; 인지된 식별가능성; 정서적 사회적 실재감